The Effect of Green Marketing Strategy on Customer Loyalty Mediated by Brand Image - Kewakuma, Angeline Stella Ventari; Rofiaty, Rofiaty; Ratnawati, Kusuma (Universitas Muhammadiyah Yogyakarta, 2021)
This research aims to know the role of brand image to mediate the influence of green marketing on The Body Shop brand loyalty of beauty products. This research was conducted with 150 respondents in the city of Malang and used the purposive sampling method. Methods of data collection used a questionnaire distributed through google forms. The data analysis technique used was Structural Equation Model (SEM) with Partial Least Square (PLS) approaches. Based on the results, green marketing had a positive and significant impact on brand image. Green marketing had a positive and significant impact on consumer loyalty. The brand image had a positive and significant impact on consumer loyalty. The brand image could significantly mediate the influence of green marketing on consumer loyalty beauty products of The Body Shop. These results revealed that the greater the green marketing gained and perceived by consumers was, the greater the sense of brand image and consumer loyalty arose from The Body Shop’s consumers.